Basal Insulin Analogs versus Neutral Protamine Hagedorn for Type 2 Diabetics - Fishel Bartal, Michal; Ward, Clara; Refuerzo, Jerrie S.; Ashimi, Sunbola S.; Joycelyn, Cornthwaite A.; Chen, Han-Yang; Chauhan, Suneet P.; Sibai, Baha M. (American Journal of Perinatology, 2020)
Objective To determine whether basal insulin analogs reduce the rate of composite neonatal morbidity compared with neutral protamine Hagedorn (NPH) in women with type 2 diabetes mellitus (T2DM).Study Design This was a retrospective cohort study of women with T2DM and singleton pregnancy at a single tertiary center. Primary outcome was a composite neonatal morbidity of any of the following: shoulder dystocia, large for gestational age, neonatal intensive care unit admission, neonatal hypoglycemia, or respiratory distress syndrome. Secondary outcomes were rates of maternal hypoglycemic events, hypertensive disorders, preterm birth, and primary cesarean delivery. Adjusted relative risk (aRR) and 95% confidence intervals (CI) were calculated.Results Of 233 women with T2DM that met the inclusion criteria, 114 (49%) were treated with basal insulin analogs and 119 (51%) with NPH. The rate of composite neonatal morbidity was similar between groups (73 vs. 60%; aRR: 1.18; 95% CI: 0.92–1.51). There were no differences in the rates of maternal adverse outcomes between the groups. Basal insulin analog was associated with a lower rate of primary cesarean delivery as compared with NPH (21 vs. 36%; aRR: 0.44; 95% CI: 0.25–0.78).Conclusion Among pregnant women with T2DM managed with either basal or NPH insulin regimen, the rates of composite neonatal morbidity and maternal complications were similar.
Keywords: diabetes; insulin; preterm birth; large for gestational age; neonatal hypoglycemia